Branching fraction measurements of the rare B0s→ϕμ+μ− and B0s→f′2(1525)μ+μ− decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2021)
The branching fraction of the rare B0s→ϕμ+μ− decay is measured using data collected by the LHCb experiment at center-of-mass energies of 7, 8, and 13 TeV, corresponding to integrated luminosities of 1, 2, and 6 fb−1, respectively. The branching fraction is reported in intervals of q2, the square of the dimuon invariant mass. In the q2 region between 1.1 and 6.0 GeV2/c4, the measurement is found to lie 3.6 standard deviations below a standard model prediction based on a combination of light cone sum rule and lattice QCD calculations. In addition, the first observation of the rare B0s→f′2(1525)μ+μ− decay is reported with a statistical significance of 9 standard deviations and its branching fraction is determined.
Im Titel sind "0", "+" und "-" hochgestellt, "s" und "2" in f′2 tiefgestellt
LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, N. Meinert, A.B. Morris, S. Neubert, M. Schmelling, D.J. Unverzagt, U. Uwer, H. Viemann, R. Waldi, C. Wang, L. Witola, M. Zavertyaev, A. Zhelezov, und weitere 941
Gesehen am 12.11.2021